”Liikunnanohjaajan työkenttä moninaistuu vuosi vuodelta” Temaattinen analyysi liikunnanohjaajien (AMK) tulevaisuuden osaamistarpeista vuonna 2035 - von Weissenberg, Patrik (2025)
von Weissenberg, P. 2025. "The field of sports instructors diversifies every year" Thematic analysis of the future competence needs of sports instructors (BSS, Bachelor of Sports Studies) in 2035. Faculty of Sport Sciences, University of Jyväskylä, Social Sciences of Sports, 61 pp., 1 appendix.